PENATAAN TEPIAN SUNGAI CENRANAE DENGAN PENDEKATAN EKOLOGIS DI KOTA SENGKANG - Setianingsih, Sri; Ersina, Sriany (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2015)
The banks of the river is one of spaces that is often used as a place for a variety of urban community activities. Utilization of the riverbank has undergone many physical changes. In order to cause a change in the environmental value increasing irregularly. Today many cities in Indonesia applying Ecological aspects as one of the most important aspects in designing of an urban space . With an ecological approach to the idea of urban design concept is applied to the banks of the River Cenranae expected to become environmentally sound urban space and has a value of Eco -Sustainable in Sengkang city.